Online Social Networking: Users Attitude and Perception - shukri, Sakinah mohd; Abdalazia, Maha Mustafa Omar; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The prime aim of this investigate is to investigate the vital factors having effect on attitudes towards social networking advertising particularly when users having a negative attitude. Composed model having variables like demographic factors i.e gender, age group, education level, usage, in formativeness and entertainment. The result of this research indicates that the three factors in formativeness, entertainment affect attitudes towards social networking advertising. The other factors gender, age and education do not affect attitudes towards social networking advertising. It is also concluded that if the received information in entertaining only then users look for information.